2016
DOI: 10.1016/j.jhazmat.2016.05.057
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation of organic arsenic compounds and their degradation products during struvite formation

Abstract: Roxarsone (ROX) and arsanilic acid (ASA) have been extensively used as organoarsenic animal feed additives. Organic arsenic compounds and their degradation products, arsenate (As(V)) and arsenite (As(III)), exist in the effluent from anaerobic reactors treating animal manure contaminated by ROX or ASA with ammonium (NH4(+)-N) and phosphate (PO4(3-)-P) together. Therefore, arsenic species in the effluent might be involved in the struvite formation process. In this study, the involvement of organic arsenic compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 37 publications
1
0
0
Order By: Relevance
“…The removal mechanism of sulfide and arsenic by coagulation is summarized in Table 2. A remarkable peak around 43.82 eV could also be observed with the help of X-ray spectra, which represents As(III) 3d orbit. The results of high-resolution XPS scan revealed that As(III) was the main form of arsenic in the liquid digestate and could be efficiently removed during ferric coagulation, which was consistent with the results of previous research on the form of arsenic in the anaerobic conditions (Lin, Yuan, Wang, Hu, & Yu, 2016).…”
Section: Research Articlesupporting
confidence: 90%
“…The removal mechanism of sulfide and arsenic by coagulation is summarized in Table 2. A remarkable peak around 43.82 eV could also be observed with the help of X-ray spectra, which represents As(III) 3d orbit. The results of high-resolution XPS scan revealed that As(III) was the main form of arsenic in the liquid digestate and could be efficiently removed during ferric coagulation, which was consistent with the results of previous research on the form of arsenic in the anaerobic conditions (Lin, Yuan, Wang, Hu, & Yu, 2016).…”
Section: Research Articlesupporting
confidence: 90%
“…To abate and manage the challenges of arsenic in the environment several studies have explored methods for the removal of arsenic from water. These techniques include ion exchange [15], reverse osmosis [16], coagulation [17], precipitation [18], electro-sorption [19], and adsorption [20]. However, most of these technologies suffer from disadvantages including the generation of toxic sludge and high costs of operation and maintenance.…”
Section: Introductionmentioning
confidence: 99%